2019
DOI: 10.1371/journal.pmed.1002913
|View full text |Cite
|
Sign up to set email alerts
|

Planned mode of delivery after previous cesarean section and short-term maternal and perinatal outcomes: A population-based record linkage cohort study in Scotland

Abstract: BackgroundPolicy consensus in high-income countries supports offering pregnant women with previous cesarean section a choice between planning an elective repeat cesarean section (ERCS) or attempting a vaginal birth, known as a planned vaginal birth after previous cesarean (VBAC), provided they do not have contraindications to planned VBAC. However, robust comprehensive information on the associated outcomes to counsel eligible women about this choice is lacking. This study investigated the short-term maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 40 publications
6
56
1
3
Order By: Relevance
“…Популяционное шотландское исследование (2019) показало, что роды через естественные родовые пути, особенно индуцированные, в сравнении с элективным КС ассоциированы с повышением риска (р < 0,05) таких осложнений, как разрыв матки (0,24% и 0,40% соответственно), необходимость в гемотрансфузии (1,14% и 0,50%), послеродовой сепсис (0,27% и 0,17%), неблагоприятные перинатальные исходы (7,99% и 6,37%) и т. д. [20]. Однако очевидно, что абсолютный риск данных осложнений крайне низок, и это созвучно результатам других исследований [10,21].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Популяционное шотландское исследование (2019) показало, что роды через естественные родовые пути, особенно индуцированные, в сравнении с элективным КС ассоциированы с повышением риска (р < 0,05) таких осложнений, как разрыв матки (0,24% и 0,40% соответственно), необходимость в гемотрансфузии (1,14% и 0,50%), послеродовой сепсис (0,27% и 0,17%), неблагоприятные перинатальные исходы (7,99% и 6,37%) и т. д. [20]. Однако очевидно, что абсолютный риск данных осложнений крайне низок, и это созвучно результатам других исследований [10,21].…”
Section: Discussionunclassified
“…В сочетании с интранатальными механизмами инициа-ции адаптационно-регуляторных механизмов плода, определяющих его будущее здоровье и жизнедеятельность [22], это невозможно переоценить. Следует учитывать также, что КС ассоциировано с серьезными кратко-и долгосрочными осложнениями как для матери, так и для ребенка [3,7,20].…”
Section: Discussionunclassified
“…Other authors have found results similar to ours: postoperative morbidity was more pronounced in patients who had an emergency cesarean than in those who had a scheduled cesarean. The difference was statistically significant (p <0.001), Ugwe E et al, in his work reported 7.6% of parietal infection in the group of caesareans made in emergencies against 1.4% for scheduled cesareans, Kathryn E et al 39,41,46 In 2019 also found in his study that the risk of having a puerperal infection was significant during cesarean after attempting the vaginal route than in scheduled cesarean, London MB et al 35 In 2004 reported that the complication that dominated the postpartum period was endometritis in the group of caesarean sections performed in an emergency after attempted vaginal delivery. In this work, we did not record maternal deaths in the two groups during the study period, we justify this by the immediate and adequate management by cesarean section of those parturients who came in emergency when their cesarean section should be scheduled.…”
Section: Maternal Morbidity and Mortality Of Caesarean Sections Perfomentioning
confidence: 90%
“…Our study correlates with study done by Fitzpatrick KA et al in UK, wherein women embark for a repeat caesarean section with a history of previous caesarean section. 4 Though the maternal and perinatal morbidity is present with VBAC the absolute risk of adverse outcomes is small and this information can be used to counsel and manage the increasing number of women with previous caesarean section. 4…”
Section: Satisfaction With the Mode Of Deliverymentioning
confidence: 99%
“…4 Though the maternal and perinatal morbidity is present with VBAC the absolute risk of adverse outcomes is small and this information can be used to counsel and manage the increasing number of women with previous caesarean section. 4…”
Section: Satisfaction With the Mode Of Deliverymentioning
confidence: 99%